Legal protection for abandoned children - Adensi Timomor,; Wenly R. J. Lolong, (Technium Social Sciences Journal, 2023)
Every child has the right to survive, grow and develop and is entitled to protection from various forms of violence, both physical and non-physical. Forms of violence and discrimination have often occurred in society. This raises concern because it is the parents or the child's relatives who carry out the neglect of the child because his biological parents have left him. In terms of children's rights are part of human rights that must be guaranteed, protected and fulfilled by parents, family, community, state and government. The purpose of this study is to find out how legal protection is for neglected children and whether parents can be subject to sanctions. While the method used in this research is normative law research or library research. The results of the study show that child neglect is a crime and can be subject to criminal sanctions. Meanwhile, the form of legal protection for neglected children is through the formation of laws and regulations, and through law enforcement efforts. Therefore in accordance with Article 26 of Law Number 23 of 2002 as amended by Law Number 35 of 2014 that children must be protected and educated without violence. It is even explained that it is the obligation of parents to look after their children and their rights as children.